A Data-Parallel Algorithm to Reliably Solve Systems of Nonlinear Equations - Goualard, F.; Goldsztejn, A. (2008 Ninth International Conference on Parallel and Distributed Computing, Applications and Technologies, 2008)
Numerical methods based on interval arithmetic are efficient means to reliably solve nonlinear systems of equations. Algorithm bc3revise is an interval method that tightens variables' domains by enforcing a property called box consistency. It has been successfully used on difficult problems whose solving eluded traditional numerical methods.We present a new algorithm to enforce box consistency that is simpler than bc3revise, faster, and easily data parallelizable. A parallel implementation with Intel SSE2 SIMD instructions shows that an increase in performance of up to an order of magnitude and more is achievable.